A novel fluorescence sensor for milk clotting enzyme chymosin using peptide as substrate and covalent organic framework nanosheet as fluorescence quencher - Xiaokang Lu; Tianle Qi; Linjiang Guo; Lin Xiao; Hanbin Xu; Guobao Ning; Hui Zhao; Canpeng Li (Food Science and Human Wellness)
Chymosin is one of the critical enzymes in cheese making. Herein, we proposed a novel fluorometric assay for chymosin determination. Firstly, covalent organic frameworks (COF) were synthesized and exfoliated to 2-dimensional COF nanosheets (COF NS) by ultrasound treatment. Gold nanoparticles (Au NPs) were loaded with COF NS to prepare AuNPs/COF NS (Au@COF NS). Secondly, rhodamine B (RhB) modified substrate peptide (Pep) for chymosin was linked with Au@COF NS to construct a Pep-Au@COF NS nanocomposite. For the sensing principle, fluorescence of RhB was quenched by Au@COF NS and the fluorescence intensity was weak due to the fluorescence resonance energy transfer between COF NS and RhB of Pep. However, in the presence of chymosin, the RhB was released by specific cleavage of the substrate peptide by chymosin and resulted in the recovery of fluorescence. The increased fluorescence intensity was proportional to the increase of chymosin concentration and thus a "turn on" fluorescent sensor for chymosin was constructed. The sensor showed a linear range in the concentration of 0.05-60.00 μg/mL for the detection of chymosin with a detection limit of 20 ng/mL. The sensor was used to quantify chymosin in rennet product with good selectivity, which has the potential applications in cheese manufacturing.